Potential and Challenges of Renewable Energy Management: Socio-economic Perspective in Indonesia - Ghazali, Rahmat; Yusuf Y.S, Muhammad; Said, Samsuardi; Darwin, Dirmansyah (PT. Riset Press International, 2025)
Renewable energy in Indonesia has great potential to reduce dependence on fossil fuels and combat climate change. Despite abundant resources such as solar, wind, and biomass, regulatory, infrastructure, and investment challenges still hamper its development. This study uses a qualitative approach to explore the state of renewable energy and its socio-economic impacts. The results and analysis show that renewable energy development can increase energy access, create jobs, and reduce greenhouse gas emissions. Collaboration between the government, private sector, and communities is essential for a successful transition. Recommendations include improving policies, increasing investment, and public education to ensure more equitable and sustainable benefits from renewable energy in Indonesia.